Family As The Basis Of National Education: An Islamic Perspective - Samsul Huda; Muhammad Syakur; Joni; Muh. Baehaqi; Sumarjoko; Husna Nashihin (At Turots: Jurnal Pendidikan Islam, 2026)
The article “Family as the Basis of National Education: An Islamic Perspective” emphasizes that the family is the first and foremost educational institution with a strategic role in instilling values of faith, morality, and nationalism from an early age. Amid the challenges of globalization and the moral crisis facing the younger generation, the family functions as a madrasah ula (the first school) that shapes children’s character through role modeling, affection, communication, and the habituation of noble values. In the Islamic perspective, national education cannot be separated from religious teachings, as both complement each other; values such as justice, brotherhood (ukhuwah), tolerance, consultation (musyawarah), and social responsibility are not only moral pillars but also foundations for national unity. Through parental example, children learn love for the homeland, social responsibility, respect for diversity, and the spirit to contribute to community life. Family-based education that integrates Islamic and national values provides a strong foundation for creating a generation with noble character, religious commitment, and nationalism, while also caring for the integrity of the nation. In conclusion, the family serves not only as a place of nurturing but also as a center for shaping identity, character, and national spirit that is harmonious, inclusive, and relevant for building a just, prosperous, and civilized society.